Virtual History: Alternatives and Counterfactuals - Ferguson, Niall (London Penguin, 1997)
What if Britain had stayed out of the First World War? What if Germany had invaded Britain in 1940? What if Nazi Germany had defeated the Soviet Union? How would England look if there had been no Cromwell? What if there had been no American Revolution? And what if John F. Kennedy had lived? In this acclaimed book, leading historians from Andrew Roberts to Michael Burleigh challenge the complacency of traditional accounts, exploring what might have been if nine of the most decisive moments in modern history had never happened.
Keywords: Historiography